Recurrent Gastrointestinal Bleeding from Dieulafoys Lesions in a Patient with Type 1 von Willebrand Disease: A Rare Association - Cardoso,Mariana Ferreira (2019)
Von Willebrand disease (vWD) is the most prevalent hereditary bleeding disorder, affecting 0.6-1.3% of the population. While gastrointestinal bleeding from angiodysplasia is a well-known complication of vWD, the same is not true for Dieulafoys lesions (DLs). We report the case of a 21-year-old black male with type 1 vWD and 2 previous hospital admissions for severe anemia with no visible blood loss. In both episodes, DLs were identified and treated endoscopically, one in the stomach and another in the duodenum. The patient presented to the emergency department in September 2016 with dizziness, fatigue, and again no visible blood loss. He was hemodynamically stable, and laboratory workup showed a hemoglobin level of 3.4 g/dL. After transfusion of packed red blood cells, intravenous iron, and von Willebrand factor/factor VIII concentrate infusions, the patient underwent upper endoscopy and colonoscopy, which were normal. Small-bowel capsule endoscopy showed dark blood and a fresh clot in the proximal jejunum. At this site, push enteroscopy identified a pulsatile vessel with an overlying minimal mucosal defect, consistent with a DL, type 2b of the Yano-Yamamoto classification, which was successfully treated with adrenaline and 2 hemoclips. The patient remains stable after 18 months of follow-up, with a hemoglobin level of 13.2 g/dL. This is a case of recurrent severe occult gastrointestinal bleeding from multiple DL in a young patient with vWD who is otherwise healthy. Three other cases of DL bleeding in the setting of vWD have been reported in the literature, suggesting a possible association between these 2 entities.